(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
FDI may be defined as an investment involvinga lasting interest and control by an investor who is a resident of anothereconomy, other than that of the host economy. In the simple sense, FDI impliedthat the investor has a significant degree of influence on the management.Foreign Direct Investments are investments made by residents of one economywith the objective of establishing a lasting interest in a company located inanother economy (host economy).